Purification of Fine Powders by a Superconducting HGMS With Vibration Assistance. (2000) - Wang, Yanmin; Johansson, Ann-Cathrine; Forssberg, Eric; Chan, Billy
Abstract : In this study, a superconducting high gradient magnetic separator (HGMS) with a matrix vibration system in dry mode was utilised to purify fine calcite and quartz powders smaller than 38 µm. The effects of the operating parameters (particle size, magnetic field/average air velocity ( B o / V o ), the amplitude of vibration as well as the aperture size of the expanded metal matrix) have been presented. The mechanicallybased matrix vibration with the air blowing was recognised to be effective for dry purification of fine powdered materials at high magnetic fields. The function of the matrix vibration has been discussed. In addition, the results have been empirically correlated with the operating parameters used for the purification in the separator.